2019
DOI: 10.33480/pilar.v15i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Penyeleksian Jurusan Terfavorit Pada SMK Sirajul Falah Dengan Metode Saw

Abstract: SMK Sirajul Falah is a Vocational High School located in the Bogor area. However, the selection of the favorite majors in SMK Sirajul Falah is still qualitative so that the process of choosing the favorite majors become not accurate. This is what makes the need for a method that is able to manage the data of the selection of the favorite majors and generate a ranking of the calculation of the weight of the selection of the favorite majors. In the selection of these favorite majors, there is a method of Simple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 1 publication
0
3
0
6
Order By: Relevance
“…Untuk menentukan jurusan yang paling disukai di SMK Sirajul Falah bisa memanfaatkan informasi kuantitatif yaitu informasi kreatifitas, nilai, kecekatan, ekstrakulikuler, dan prestasi dari setiap jurusan, seperti Pemasaran (PM), Akuntansi (AK), Administrasi Perkantoran (AP), serta Teknik Komputer & Jaringan (TKJ). Hasil akhir dari penelitian tersebut adalah salah satu yang signifikan akan menjadi jurusan yang paling disukai di SMK Sirajul Falah adalah jurusan Akuntasi yang mendapatkan nilai akhir perhitungan sebesar 27% [6].…”
Section: Tinjauan Pustaka Dan Teori 21 Tinjauan Pustakaunclassified
“…Untuk menentukan jurusan yang paling disukai di SMK Sirajul Falah bisa memanfaatkan informasi kuantitatif yaitu informasi kreatifitas, nilai, kecekatan, ekstrakulikuler, dan prestasi dari setiap jurusan, seperti Pemasaran (PM), Akuntansi (AK), Administrasi Perkantoran (AP), serta Teknik Komputer & Jaringan (TKJ). Hasil akhir dari penelitian tersebut adalah salah satu yang signifikan akan menjadi jurusan yang paling disukai di SMK Sirajul Falah adalah jurusan Akuntasi yang mendapatkan nilai akhir perhitungan sebesar 27% [6].…”
Section: Tinjauan Pustaka Dan Teori 21 Tinjauan Pustakaunclassified
“…Seperti penelitian yang telah dilakukan S. Siti, D. Lestari [1] merancang sistem pendukung keputusan untuk melakukan penilaian guru terbaik menggunakan metode SAW, sedangkan S. Nurlela dkk [2] menggunakan metode SAW untuk menyeleksi jurusan terfavorit pada SMK Sirajul falah. Dan A. Windarto [3] menggunakan SAW untuk menentukan penilaian kerja karyawan PTPN III Pematangsiantar .…”
Section: Frans's Alfiando Jordi Esa Putra Muhammad Fiqranunclassified
“…Therefore, a decision support system is needed that can support decisions in the distribution of zakat based on the criteria that are entitled to receive zakat so that the distribution process reaches the right person is entitled. The method used in the study was Simple Additive Weighting (SAW) [9]. The study concluded that the system could run according to the design and function that can provide the results of mustahik stamps that are entitled to receive zakat using Fuzzy Multiple Attribute Decision Making (FMADM) and Simple Additive Weighting (SAW) in accordance with the criteria set by the Committee baznas Kota Pekanbaru.…”
Section: Iaic Jiicsmentioning
confidence: 99%